Pengaruh keadilan distributif terhadap keterikatan karyawan dengan persepsi dukungan organisasi sebagai variabel mediasi pada Bank Nagari Cabang Utama Padang - Khairil Mahdi Erfad; Chichi Andriani (Universitas Negeri Padang, 2021)
AbstractThis study aims to analyze the effect of distributive justice on employee engagement with perceived organizational support as a mediating variable. The research was carried out on the employees of Bank Nagari Main Branch, amounting to 125 people who were selected using proportional random sampling formula. The analytical method used is path analysis. In the testing phase it was found that distributive justice did not have a significant effect on employee engagement, while the perception of organizational support had a significant effect on employee engagement, besides that in the test results it was also found that distributive justice had a positive effect on employee engagement with perceptions of organizational support as a mediating variable for employees of Bank employees. Nagari Main Branch of Padang. TRANSLATE with x EnglishArabicHebrewPolishBulgarianHindiPortugueseCatalanHmong DawRomanianChinese SimplifiedHungarianRussianChinese TraditionalIndonesianSlovakCzechItalianSlovenianDanishJapaneseSpanishDutchKlingonSwedishEnglishKoreanThaiEstonianLatvianTurkishFinnishLithuanianUkrainianFrenchMalayUrduGermanMalteseVietnameseGreekNorwegianWelshHaitian CreolePersian // TRANSLATE with COPY THE URL BELOW Back EMBED THE SNIPPET BELOW IN YOUR SITE Enable collaborative features and customize widget: Bing Webmaster PortalBack//